What is determining affordable housing shortages in the Greater Kuala Lumpur, Malaysia? - Abdul Lateef, Olanrewaju; Arazi, Idrus (Emerald, 2019)
Purpose The purpose of this paper is to investigate the determinants of the affordable housing shortage in the Greater Kuala Lumpur from the suppliers’ perspectives.